A Case Study on The Effects of Human Resource Shortages on Project Management in The Uk Health Sector: Focusing on Achieve Care Solutions Agency (International Journal of Scientific Research and Management (IJSRM), 2023)
The healthcare sector, one of the most in-demand sectors in the UK, is currently facing a shortage of human resources. This shortage is due to several factors, including a high turnover rate, an aging workforce, and a lack of younger staff entering the sector. This study explores the impact of human resource shortages on project management within the UK healthcare sector, focusing on Achieve Care Solutions Agency. To understand the context of this shortage, we surveyed 50 professionals from Achieve Care Solutions Agency. Out of the questions asked, 85% of the responses were properly returned. The data was then analyzed using graphical statistics to create averages, tables, and graphs showing frequency and percentages. The findings of the study suggest that training has a positive effect on the motivation of Achieve Care’s human resources. The current workforce in social care is experienced, and compassionate, and values their work, primarily because they feel appreciated and well-trained. However, the critical shortage of human resources is negatively impacting the UK’s healthcare system and organizations like Achieve Care. This study highlights the need for a healthcare delivery system adequately staffed with human resources. It emphasizes the importance of providing everyone with access to the guidance, support, and care they need to live fulfilling lives. Despite the challenges posed by human resource shortages, the healthcare sector presents a promising career path with a bright future, especially as other industries contract due to increased automation.